2005
DOI: 10.1094/phyto-95-1157
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Late Leaf Spot of Peanut (Arachis hypogaea) with Chitinolytic Bacteria

Abstract: Late leaf spot (LLS), caused by Phaeoisariopsis personata, is a foliar disease of groundnut or peanut (Arachis hypogaea) with high economic and global importance. Antifungal and chitinolytic Bacillus circulans GRS 243 and Serratia marcescens GPS 5, selected among a collection of 393 peanut-associated bacteria, were applied as a prophylactic foliar spray and tested for control of LLS. Chitin-supplemented application of B. circulans GRS 243 and S. marcescens GPS 5 resulted in improved biological control of LLS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 42 publications
1
52
0
3
Order By: Relevance
“…The microbial communities found in the phyllosphere have essential roles in processes related to plant development, for example, performing nitrogen fixation, protecting plants against invading pathogens and biosynthesizing phytohormones (Jones, 1970;Freiberg, 1998;Brandl et al, 2001;Kishore et al, 2005). It makes them important pieces of global processes, such as carbon sequestration (Bulgarelli et al, 2013), and they can be used as potential sources for the development of sustainable agricultural practices.…”
Section: Microbial Groups Living In the Phyllospherementioning
confidence: 99%
“…The microbial communities found in the phyllosphere have essential roles in processes related to plant development, for example, performing nitrogen fixation, protecting plants against invading pathogens and biosynthesizing phytohormones (Jones, 1970;Freiberg, 1998;Brandl et al, 2001;Kishore et al, 2005). It makes them important pieces of global processes, such as carbon sequestration (Bulgarelli et al, 2013), and they can be used as potential sources for the development of sustainable agricultural practices.…”
Section: Microbial Groups Living In the Phyllospherementioning
confidence: 99%
“…Microbial enzymes, especially chitinases, are highly important in biocontrol strategies due to their ability (a) to degrade chitin (the main component of the cell wall of most fungi), (b) to inhibit the germination of fungal spores and the elongation of the germinative tube, and (c) to lyse hyphae (Kishore et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are responsible for the degradation of the main polysaccharides that make up the cell wall of the fungi, by the hydrolysis of their glycosidic bonds ( Figure 5). There are currently diverse scientific studies that report the role of these enzymes in the in vitro antifungal activities obtained from strains of the Bacillus genus (Kishore et al, 2005;Shafi et al, 2017). For example, Yan et al (2011) demonstrated the role a chitinase in the control of Rhizoctonia solani by B. subtilis SL-13, evaluating the inhibitory activity of the purified enzyme, confronted with this pathogen.…”
Section: Producción De Enzimas Líticasmentioning
confidence: 99%
“…Estas enzimas son responsables de la degradación de los principales polisacáridos que conforma la pared celular de hongos, mediante la hidrólisis de sus enlaces glucosídicos (Figura 5). Actualmente, existen diversos estudios científicos que reportan el papel de estas enzimas en la actividad antifúngica in vitro obtenidas de cepas del género Bacillus (Kishore et al, 2005;Liu et al, 2010;Shafi et al, 2017). Por ejemplo, Yan et al (2011) demostraron el papel de una quitinasa en el control de Rhizoctonia solani por B. subtilis SL-13, evaluando la actividad inhibitoria de la enzima purificada y confrontada contra dicho patógeno.…”
Section: Producción De Enzimas Líticasunclassified